Disease Progression in Children With Perinatal Human Immunodeficiency Virus Correlates With Increased PD-1+ CD8 T Cells That Coexpress Multiple Immune Checkpoints. (17th April 2021) - Tailor, Janki; Foldi, Julia; Generoso, Matthew; McCarty, Bret; Alankar, Aparna; Kilberg, Max; Mwamzuka, Mussa; Marshed, Fatma; Ahmed, Aabid; Liu, Mengling; Borkowsky, William; Unutmaz, Derya; et al.
Abstract: Background: PD-1 marks exhausted T cells, with weak effector functions. Adults living with human immunodeficiency virus (HIV) have increased levels of PD-1 + CD8 T cells that correlate with HIV disease progression, yet little is known about the role of PD-1 + CD8 T cells in children with perinatal HIV. Methods: We enrolled 76 Kenyan children with perinatal HIV and 43 children who were HIV unexposed and quantified PD-1 levels on CD8 T cells; their coexpression with immune checkpoints (ICs) 2B4, CD160, and TIM3; correlates with immune activation and HIV disease progression; and HIV-specific and -nonspecific proliferative responses. Results: PD-1 + CD8 T-cell frequencies are elevated in children with perinatal HIV and associated with disease progression. The majority of PD-1 + CD8 T cells coexpress additional ICs. ART initiation lowers total PD-1 levels and coexpression of multiple ICs. The frequency of PD-1 + 2B4 + CD160 + TIM3 – in PD-1 + CD8 T cells predicts weaker HIV-specific proliferative responses, suggesting that this subset is functionally exhausted. Conclusions: Children with perinatal HIV have high levels of PD-1 + CD8 T cells that are a heterogeneous population differentially coexpressing multiple ICs. Understanding the complex interplay of ICs is essential to guide the development of PD-1–directed immunotherapies for pediatric HIV remission and cure. Abstract : Children with perinatal HIV have high levels of PD-1 + CD8 T cells that coexpress multiple other immune checkpoints. Each subpopulation correlates differently with clinical markers of HIV, T-cell activation, and CD8 T-cell function, suggesting distinct roles in HIV pathogenesis.